The Carotenoid Esterification Gene BrPYP Controls Pale-Yellow Petal Color in Flowering Chinese Cabbage (Brassica rapa L. subsp. parachinensis) - Li, Peirong; Lv, Sirui; Zhang, Deshuang; Su, Tongbing; Xin, Xiaoyun; Wang, Weihong; Zhao, Xiuyun; Yu, Yangjun; Zhang, Yaowei; Yu, Shuancang; Zhang, Fenglan (Frontiers in Plant Science, 2022)
Carotenoid esterification plays indispensable roles in preventing degradation and maintaining the stability of carotenoids. Although the carotenoid biosynthetic pathway has been well characterized, the molecular mechanisms underlying carotenoid esterification, especially in floral organs, remain poorly understood. In this study, we identified a natural mutant flowering Chinese cabbage (Caixin, Brassica rapa L. subsp. chinensis var. parachinensis) with visually distinguishable pale-yellow petals controlled by a single recessive gene. Transmission electron microscopy demonstrated that the chromoplasts in the yellow petals were surrounded by more fully developed plastoglobules compared to the pale-yellow mutant. Carotenoid analyses further revealed that, compared to the pale-yellow petals, the yellow petals contained high levels of esterified carotenoids, including lutein caprate, violaxanthin dilaurate, violaxanthin-myristate-laurate, 5,6epoxy-luttein dilaurate, lutein dilaurate and lutein laurate. Based on bulked segregation analysis and fine mapping, we subsequently identified the critical role of a phytyl ester synthase 2 protein (PALE YELLOW PETAL, BrPYP) in regulating carotenoid pigmentation in flowering Chinese cabbage petals. Compared to the yellow wild-type, a 1148 bp deletion was identified in the promoter region of BrPYP in the pale-yellow mutant, resulting in down-regulated expression. Transgenic Arabidopsis plants harboring beta-glucuronidase (GUS) driven by yellow (BrPYPY::GUS) and pale-yellow type (BrPYPPY::GUS) promoters were subsequently constructed, revealing stronger expression of BrPYPY::GUS both in the leaves and petals. Furthermore, virus-induced gene silencing of BrPYP significantly altered petal color from yellow to pale yellow. These findings demonstrate the molecular mechanism of carotenoid esterification, suggesting a role of phytyl ester synthase in carotenoid biosynthesis of flowering Chinese cabbage.